Keunggulan Kompetitif Teknologi Modular Rumah Instan Sederhana Sehat (RISHA) Jayagiri - Mia Wimala; Benjamin Bonardo; Wisena Perceka; Carissa Carissa (Arsitektura : Jurnal Ilmiah Arsitektur dan Lingkungan Binaan, 2022)
The RISHA applied to the Jayagiri house was compared with conventional technology, in terms of construction duration, costs, and environmental friendliness. The strength of the RISHA structure was be analyzed based on existing standards using SAP2000 and spColumn. The data were the literature studies and interviews with RISHA users, applicators, and the Directorate of Engineering Affairs for Human Settlements and Housing. Compared to conventional, the Jayagiri house is proven to be more eco-friendly with an efficiency value of 48.6 points. It was also built four weeks faster, with a lower cost of IDR123,043.90 per square meter, or 3.97%. The strength analysis shows that the capacity of the column reinforcement is still capable of carrying the designed load, the anchorage capacity of the X-direction beam has not met the requirements.